Epitope Based Vaccine Designing- A mini review - Sunil K Arora; Aryandra Arya (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
A vaccine is an antigen derived from pathogen. In its crudest form vaccine contains either attenuated pathogen, or an antigen molecule as in case of subunit vaccine,  yet what interacts with immune system are few amino acids in the form of epitopes [1]. The idea to form a vaccine from selective few epitopes has emerged as a more logical approach owing to the fact that the conventional approaches are slow and selection of antigen is more or less random. In the last 5 years a lot of new vaccine candidates have been proposed which are based on B Cell Epitopes (BCE) and T Cell Epitopes (TCE) [2]. This approach of rapid identification of immuno epitopes is centered on computational predictions, which utilize advance algorithms and increasing epitope data base. Epitope prediction is one of the most important corner stone of in-silico vaccine designing, however it depends on antigen identification, and most crucially epitope selection for an effective immune response.